High efficient beam cleanup based on stimulated Brillouin scattering with a large core fiber. (15th September 2014) - Gao, Qilin; Lu, Zhiwei; Zhu, Chengyu; Zhang, Jianhui
Abstract: A novel approach of beam cleanup based on stimulated Brillouin scattering with a large core fiber is proposed to improve the laser beam quality. The fusion splice scheme from a single-mode fiber to a very large core fiber (105 µm) is first employed in stimulated Brillouin scattering to steadily excite the fundamental mode of the Stokes beam. As a result, the output beam achieves a measured M 2 value of around 1.3 meanwhile the pump conversion efficiency is up to 90%, which is the best in the reports of stimulated Brillouin scattering cleanup to our knowledge.